El pueblo mapuche: relación con el Estado chileno y regímenes de representación - Cerro Fernández, Raúl (2024)
The present work is concerned with analyzing the relationship between the Mapuche and the Chilean State. For this purpose, the research is divided into three parts. First, the history of the dispossession suffered by the Mapuches after Chile's independence, due to the prioritization of national unity by state agencies. Second, the evolution of the Chilean State's treatment of this indigenous people, which went from usurpation to neoliberal multiculturalism. Finally, the configuration of the Mapuche sociocultural identity in the face of colonialist threats on the basis of two bastions, territory and autonomy. This has had an impact on the type of representation they currently have with Chilean political parties and institutions. Consequently, the question of Mapuche representation is far from being resolved.